Call to needle times after acute myocardial infarction in urban and rural areas in northeast Scotland: prospective observational study. Issue 7158 (29th August 1998) - Rawles, John; Sinclair, Catherine; Jennings, Kevin; Ritchie, Lewis; Waugh, Norman
Abstract: Objective : To determine call to needle times and consider how best to provide timely thrombolytic treatment for patients with acute myocardial infarction. Design : Prospective observational study. Setting : City, suburban, and country practices referring patients to a single district general hospital in northeast Scotland. Subjects : 1046 patients with suspected acute myocardial infarction given thrombolytic treatment. Main outcome measures : Time from patients' calls for medical help until receipt of opiate or thrombolytic treatment, measured against a call to needle time of 90 minutes or less, as proposed by the British Heart Foundation. Results : General practitioners were the first medical contact in 97% (528/544) of calls by country patients and 68% (340/502) of city and suburban patients. When opiate was given by general practitioners, median call to opiate time was about 30 minutes (95% within 90 minutes) in city, suburbs, and country; call to opiate delay was about 60 minutes in city and suburban patients calling "999" for an ambulance. One third of country patients received thrombolytic treatment from their general practitioners with a median call to thrombolysis time of 45 minutes (93% within 90 minutes); this compares with 150 minutes (5% within 90 minutes) when this treatment was deferred until after hospital admission. In the city and suburbs, no thrombolytic treatment was given outside hospital, and only a minority of patients received it within 90 minutes of calling; median call to thrombolysis time was 95 (46% within 90 minutes) minutes. Conclusions : The first medical contact after acute myocardial infarction is most commonly with a general practitioner. This contact provides the optimum opportunity to give thrombolytic treatment within the British Heart Foundation's guideline.